Retrospective analysis of ichthyofauna of the Desnyansko-Starogutskyi national natural park - A. Roman; Yu. Kutsokon; M. Shcherbatiuk (Ribogospodarsʹka Nauka Ukraïni)
Purpose. Elucidation of qualitative and quantitative parameters of ichthyofauna of the Desnyansko-Starogutskyi NNP with the brief analysis of main changes in the structure and distribution of fishes.